A modified loop-mediated isothermal amplification method for detecting avian infectious laryngotracheitis virus. Issue 6 (1st December 2021) - Yu, Jifeng; Xie, Jing; Cao, Ye; Kang, Runmin; Lin, Yi; Wei, Yong; Liao, Dangjin; Li, Xingyu; Ye, Yonggang; Pan, Meng; Xiao, Lu; Ye, Jianqiang
Abstract: This study was aimed to establish a highly specific and sensitive loop-mediated isothermal amplification (LAMP) method for diagnosing avian infectious laryngotracheitis (AILT). DNA was extracted from isolated infectious laryngotracheitis virus (ILTV) strains and control samples, followed by PCR using three sets of six specific primers. The detection efficiency of the LAMP assay was evaluated by the turbidity and calcein methods. The sensitivity of LAMP was then assessed using a concentration gradient followed by a specificity analysis. Furthermore, the detection efficiency of LAMP and PCR was compared. Finally, a clinical test was performed to evaluate the value of the LAMP assay. The optimal temperature for the LAMP reaction was 66 °C. Meanwhile, the primers selected for the LAMP assay were highly specific for the target virus. The sensitivity of the turbidity and calcein methods for LAMP was consistent. The minimum detection concentration of LAMP was 0.06 pg/μL, which was 100-fold higher than that of PCR. Furthermore, the results from clinical samples showed that the LAMP method could identify AILT from many samples. The newly designed LAMP assay was an effective method for AILT detection at an optimal temperature of 66 °C with a minimum detection concentration of 0.06 pg/µL.